Morphologic and Chemical Properties of PMMA/ATH Layers with Enhanced Abrasion Resistance Realised by Cold Plasma Spraying at Atmospheric Pressure - L. Wallenhorst; R. Rerich; M. Vovk; S. Dahle; H. Militz; G. Ohms; W. Viöl (Advances in Condensed Matter Physics)
This study investigated the morphologic and chemical properties of coatings based on PMMA/ATH powder and deposited by cold plasma spraying on wood and glass. Since the deposition of pure PMMA/ATH powder with air as process gas yielded coatings with insufficient abrasion resistance, two modifications of the basic process were investigated. Previous studies showed that replacing air as process gas with forming gas did not enhance the abrasion resistance, but the addition of a phenol-formaldehyde resin (PF) succeeded in stabilising the particle coatings. In this work, results from morphologic and chemical analysis suggested an encasement of the PMMA/ATH particles by plasma-modified PF and thus a fusion of individual particles, explaining the enhanced bonding. Moreover, adhesion tests confirmed an outstanding bonding between the coating and wood as well as glass, which is assumed to result from interactions between the PF’s hydroxyl groups and functional groups on the substrates’ surfaces. Studies on the wettability revealed a hydrophobic character of such coatings, therefore generally indicating a possible application, for example, to reduce water uptake by wooden materials.